(The Effect of Catalyst, Temperature and Process Duration on The Production of Methyl Ricinoleate from Castor Oil) - Hitler Guring Pohan; Eko Susanto; Gasik Darma (Balai Besar Industri Agro, 1991)
Methyl ricinoleate was produced by methanolysis process from castor oil using KOH and NaOH as catalysts. The esterification process was carried out at the temperature of 30 derajat and 70 derajat celcius for 1, 2, and 3 hrs respectively. The product was analyses using GC for the esterification process. The iod value saponification value, and acid number were also analysed. Potassium hydroxide gave higher result in comparison to sodium hydroxide as catalyst for the process duration of 3 hrs. The specific gravity of the product ranged from 0.8903 to 0.9608 and the refractive index was between 1.3810 and 1.4500.